The validation of culturally appropriate scales to assess the family health climate in a multi-ethnic Asian population - Ho, Yi-Ching Lynn; Chew, Mary Su-Lynn; Ho, Clement Zhong-Hao; Latib, Aisyah Binte; Lee, Vivian Shu-Yi; Lin, Gladis Jing; Thumboo, Julian; Doshi, Kinjal (Frontiers in Public Health, 2022)
Background: The Family Health Climate (FHC) is a family environment attribute postulated to influence the health behaviors of family members. It can be measured by domain scales for physical activity (FHC-PA) and nutrition (FHC-NU), which have been validated and used to identify health climate patterns in families in Western populations. To extend the use of the scales to Asian settings, this study aimed to adapt and validate the instruments for use in the multi-ethnic population of Singapore, accounting for language and cultural differences. Methods: In Part A (n=40) to adapt the scales for the Singapore population, we performed cognitive interviews, face validity testing and pre-testing of the instruments (n=40). Besides English, the scales were translated into Chinese and Malay. In Part B (n=400), we performed exploratory and confirmatory factor analyses respectively on two random samples. We also tested for item discriminant validity, internal consistency reliability, construct validity, and measurement invariance. Results: The findings from the cognitive interviews in Part A led to scale adaptations to accommodate cultural and linguistic factors. In Part B, EFA on Sample I resulted in a three-factor model for the PA scale (accounting for 71.2% variance) and a four-factor model for the NU scale (accounting for 72.8% variance). CFA on Sample II indicated acceptable model fits: FHC-PA: χ2=192.29, df=101, p<.001, χ2/df=1.90; SRMR=0.049; RMSEA=0.067; CFI=0.969; TLI=0.963; FHC-NU: χ2=170.46, df=98, p<.001, χ2/df=1.74; SRMR=0.036; RMSEA=0.061; CFI=0.967; TLI=0.960. The scores of family members demonstrated significant agreement on the FHC-PA (Sg) (ICC(2,2)=0.77) and FHC-NU (Sg) (ICC(2,2)=0.75) scales. Findings suggest good evidence for item discriminant validity, internal consistency reliability, construct validity, and measurement invariance. Short versions of the scales were also developed. Conclusions: We adapted, translated and validated the scales for assessing the health climate of families in Singapore, including the development of short versions. The results showed good psychometric properties and the constructs had significant relationships with health behaviors and routines. Improving our understanding of family influences on individual health behavior will be important in developing multi-level strategies for health promotion and chronic disease prevention.